Modeling and simulation of CO2 methanation in a fixed-bed reactor: Evaluation of 1D pseudo-homogeneous approaches. - Sanz Monreal, Pablo; Mercader Plou, Víctor Daniel; Durán Sánchez, Paul Esteban; Francés Pérez, Eva; Herguido Huerta, Javier; Peña Llorente, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2025)
Several one-dimensional fixed-bed reactor models were simulated to evaluate their accuracy in CO2 methanation. A parametric study identified mass and heat transfer coefficients that best fit experimental data. Including axial transport effects was essential to reproduce observed trends, and separating their contributions clarified their individual impact on reactor performance.